2017
DOI: 10.1016/j.molp.2017.02.009
|View full text |Cite
|
Sign up to set email alerts
|

SNOWY COTYLEDON 2 Promotes Chloroplast Development and Has a Role in Leaf Variegation in Both Lotus japonicus and Arabidopsis thaliana

Abstract: Plants contain various factors that transiently interact with subunits or intermediates of the thylakoid multiprotein complexes, promoting their stable association and integration. Hence, assembly factors are essential for chloroplast development and the transition from heterotrophic to phototrophic growth. Snowy cotyledon 2 (SCO2) is a DNAJ-like protein involved in thylakoid membrane biogenesis and interacts with the light-harvesting chlorophyll-binding protein LHCB1. In Arabidopsis thaliana, SCO2 function wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 61 publications
2
37
0
Order By: Relevance
“…Thus, it was suggested that the defects are specific to the development of chloroplasts from proplastids/eoplasts in cotyledons, and SCO proteins were assumed to be cotyledon-specific factors (Waters and Langdale, 2009). However, under short-day conditions, smaller and pale-green true leaves can be observed in sco2 mutants, and disruption of SCO2 in Lotus japonicus results not only in paler cotyledons but also in variegated true leaves (Zagari et al, 2017).…”
Section: Pp7l Acts As a Positive Regulator Of Chloroplast Developmentmentioning
confidence: 98%
See 1 more Smart Citation
“…Thus, it was suggested that the defects are specific to the development of chloroplasts from proplastids/eoplasts in cotyledons, and SCO proteins were assumed to be cotyledon-specific factors (Waters and Langdale, 2009). However, under short-day conditions, smaller and pale-green true leaves can be observed in sco2 mutants, and disruption of SCO2 in Lotus japonicus results not only in paler cotyledons but also in variegated true leaves (Zagari et al, 2017).…”
Section: Pp7l Acts As a Positive Regulator Of Chloroplast Developmentmentioning
confidence: 98%
“…In consequence, some proteins that were previously classified as being specific for chloroplast development in cotyledons or true leaves are less specific than was once thought. More sensitive phenotyping methods like Imaging PAM analysis (this study) or the application of diverse growth conditions (as in the case of sco2; Zagari et al, 2017) will be instrumental in the future analysis of mutants that appear to be specifically affected at certain developmental stages.…”
Section: Pp7l Acts As a Positive Regulator Of Chloroplast Developmentmentioning
confidence: 99%
“…In vivo room temperature chlorophyll a fluorescence of leaves was analyzed using an Imaging PAM chlorophyll fluorometer equipped with the computer-operated PAM control unit IMAG-MAXI (Walz) as described previously (Zagari et al, 2017). The minimal fluorescence (F 0 ) was measured after acclimation for at least 30 min in the dark.…”
Section: Chlorophyll Fluorescence Measurementsmentioning
confidence: 99%
“…Genes involved in the variegation pattern formation have been cloned in monocot and dicot species (e.g. Wu et al, 1999; Chen et al, 2000; Takechi et al, 2000; Prikryl et al, 2008; Hayashi-Tsugane et al, 2014; Wang et al, 2016; Zheng et al, 2016; Guan et al, 2017; Zagari et al, 2017). Despite the advances of identifying the underlying genes, insights to the molecular mechanisms controlling the phenomenon are rare (Sakamoto, 2003; Yu et al, 2007).…”
Section: Introductionmentioning
confidence: 99%